Boosting positive mood in medical and emergency personnel during the COVID-19 pandemic: preliminary evidence of efficacy, feasibility and acceptability of a novel online ambulatory intervention. (26th April 2021) - Coifman, Karin G.; Disabato, David D; Seah, T H Stanley; Ostrowski-Delahanty, Sarah; Palmieri, Patrick A; Delahanty, Douglas L.; Gunstad, John
Abstract : Objectives: The aim of this project was to test the efficacy of a brief and novel online ambulatory intervention aimed at supporting psychological health and well-being for medical personnel and first responders during the COVID-19 pandemic. Methods: Interested participants, n=28, actively employed as medical personnel, support staff and emergency responders, in the Midwestern USA in May–June of 2020, provided informed consent and were randomised to complete either low-dose or high-dose intervention, one time daily for 1 week via smartphone application. Each daily intervention included expressive writing, adaptive emotion regulation activity and (one vs two) positive emotion-generation activities, lasting 3–6 min a day. Ratings of negative and positive emotion were provided before and after each activity daily. Analyses tested compliance, acceptability, as well as efficacy at increasing positive emotion and decreasing negative emotion with each use and across time. Results: The results indicated a 13% increase in positive emotion, t(25)=2.01, p=0.056; and decrease in negative emotion by 44%, t(25)=−4.00, p=0.001 across both doses. However, there was a clear advantage for individuals in the high-dose condition as daily boosts in positive emotion were significantly greater (an additional 9.4%) B=0.47, p=0.018. Overall, compliance was good. Acceptability ratings were good for those who completed the follow-up assessment. Conclusion: Front-line personnel, including medical staff and emergency responders, are experiencing unprecedented psychological stress during the COVID-19 pandemic. This investigation suggests both feasibility and efficacy for a brief, daily, ambulatory intervention which could provide essential psychological support to individuals at risk in the workplace.